ANALYSIS OF INTERNAL CONTROL ON REVENUE CYCLE BASED ON COSO FRAMEWORK: CASE STUDY ON TRANSPORT DIVISION PT. SEGER AGRO NUSANTARA - Adinda Septaria (Perpustakaan Universitas Surabaya, 2016)
The purpose for this research is to know how effective the internal control of revenue cycle based on COSO Framework, case study: Transport Division in PT. Seger Agro Nusantara. Recently, Transport Division changed its accounting system from MYOB into FINA Accounting Software because of business needs. However, COSO help to analyze the effectiveness of internal control in a company. This research is use qualitative. To gather information, the researcher use observation, review, and documentary analysis as the data collection method. The data collection starts from February until May 2014 in PT. Seger Agro Nusantara, Surabaya. The researcher will analyze the data and information gathered from PT. Seger Agro Nusantara by using COSO Framework. The result of evaluation by using COSO Framework is company needs to improve their internal control related to revenue cycle, such as: make a credit limit, installing GPS, do performance evaluation for employee, and others.